Penguatan Institusi Lokal dan Menggerakkan Modal Sosial Melalui Komunitas Untuk Menciptakan Kampung Berdaya - Yuliyanti, Tri (Universitas 17 Agustus 1945 Surabaya, 2018)
In carrying out its work a manager will use the concepts of management to facilitate the implementation of the task. By applying good public management practices and true, then the success of building a village will be realized. This research uses qualitative method by using the main instrument of Chairman of RW which is also Chairman of 3G Community. Some supporting instruments include observation and interview guidelines and secondary data. The conclusion of this research is to plan and implement environmental improvement in the region of Glintung, the Head of RW directly formed a community called